2016
DOI: 10.13189/ujm.2016.041207
|View full text |Cite
|
Sign up to set email alerts
|

The Determinant Factors of Employees' Behavioral Intention in Green Building Restaurants - Integration TRA and TAM

Abstract: This study integrated with technology acceptance model (TAM) and theory of reasoned action (TRA) to construct a behavior model of green building restaurants. On the basis of TAM analysis, four constructs were identified: perceived usefulness, perceived ease of use, attitude and intention. Three constructs were identified from TRA: motivation to comply, subjective norm and intention. The results shown: first, perceived usefulness, and perceived ease of use green building restaurants in Taiwan has an indirect ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
1
4
1
Order By: Relevance
“…of use, and perceived risk towards intention. This was consistent with the findings of Hansen, Jensen and Solgaard (2004) and Chuang, Chen and Chen (2016). The indirect relationship between subjective norm with intention was not as strong as its direct relationship, as its estimate or regression coefficient value was smaller (0.27 < 0.33), in line with what Hansen, Jensen and Solgaard (2004) found.…”
Section: Factors Influencing Consumers' Intention In Using Fda During...supporting
confidence: 90%
See 1 more Smart Citation
“…of use, and perceived risk towards intention. This was consistent with the findings of Hansen, Jensen and Solgaard (2004) and Chuang, Chen and Chen (2016). The indirect relationship between subjective norm with intention was not as strong as its direct relationship, as its estimate or regression coefficient value was smaller (0.27 < 0.33), in line with what Hansen, Jensen and Solgaard (2004) found.…”
Section: Factors Influencing Consumers' Intention In Using Fda During...supporting
confidence: 90%
“…Previous studies that integrated TRA and TAM on such subject regarding usage intention of certain technological product had done by Wu and Liao (2011), Ho et al (2015), and Chuang, Chen and Chen (2016). Additionally, trustworthiness and perceived risk were also included to better explain consumers' intention to use FDA during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Concluding the entire work, it can be said that this study has shown that there are some positive movements and attitudes that Bishoftu resort hotel managers showed toward environmental sustainability practices. It is further confirmed that even though managers showed some positive attitude toward the sustainability issues, the adopted practices are not in a very much satisfactory level, because they have incorporated only with four best practices: the installation of energy-efficient bulbs and key card/sensor for light; using energy-efficient appliances; the installation of dual toilet and other low-flow water technologies; reuse of items such as water for gardening and cloth napkins, buying local products significantly, while other 21 practices were not at the satisfactory level, which is in contrary to previous research [29], which indicates that positive attitude is not the only factor that secures better performance.…”
Section: Conclusion and Policy Implicationscontrasting
confidence: 89%
“…There is a relationship between top management commitment and some external and internal factors. The top management commitment can influence environmental performance [29]. Travelers' comments also affect environmental management and sustainability of hotels [30,31].…”
Section: Environmental Attitude and Behaviorsmentioning
confidence: 99%
“…There are also studies pointing out a positive relationship between perceived usefulness and attitude. In addition, attitude works as a mediator of the impact perceived usefulness has on behavioral intention [13,[33][34][35][36]. This study proposes the following two hypotheses: public understanding about the perceived usefulness of urban trees will positively influence the behavioral intention to pay to conserve urban trees and positively influence the attitude toward urban tree protection.…”
Section: Perceived Usefulnessmentioning
confidence: 99%